Lead concentration in urban dust and in leaves of street plants, Karachi - Hassan Farid; Zafar I. Shams; Farooq A. Khan (Kuwait Journal of Science)
Lead concentrations were investigated in roadside dust at 29 different designated sites of Karachi and compared them with earlier available studies from Karachi. The study reveals that the lead concentrations in the dust of the city range from 73.47 + 3.79 mg/kg to 998.66 + 11.09 mg/kg. Presently, greater lead concentrations are found in the areas that have higher number of shops of welding, soldering, printing and battery recycling. Earlier, gasoline powered vehicles were the main source of environmental lead. Currently, vehicular emission is no longer a significant source of environmental lead in Karachi, since compressed natural gas has almost completely replaced gasoline for fueling motor vehicles over the last fifteen years. Moreover, lead has been completely phased out from the gasoline in Pakistan. Lead concentrations in the leaves of four different species of plants, growing extensively in Karachi were also investigated. Statistically, significant difference was not found among the lead concentrations in the leaves of the four different species. Statistically significant correlation was not found between lead concentrations in leaves and dust of different sites. The study will help to reduce the environmental lead, particularly in the neighbourhoods that have greater lead concentration, so as to mitigate it from human exposure.